Single-Cell RNA Sequencing Reveals the Immunological Profiles of Renal Allograft Rejection in Mice - Shen, Qixia; Wang, Yucheng; Chen, Jiaoyi; Ma, Lifeng; Huang, Xiaoru; Tang, Sydney C. W.; Lan, Huiyao; Jiang, Hong; Chen, Jianghua (Frontiers in Immunology, 2021)
Allograft rejection is a common immunological feature in renal transplantation and is associated with reduced graft survival. A mouse renal allograft rejection model was induced and single-cell RNA sequencing (scRNA-seq) data of CD45+ leukocytes in kidney allografts on day 7 (D7) and day 15 (D15) after operation was analyzed to reveal a full immunological profiling. We identified 20 immune cell types among 10921 leukocytes. Macrophages and CD8+ T cells constituted the main populations on both timepoints. In the process from acute rejection (AR) towards chronic rejection (CR), the proportion of proliferating and naïve CD8+ T cells dropped significantly. Both B cells and neutrophils decreased by about 3 folds. On the contrary, the proportion of macrophages and dendritic cells (DCs) increased significantly, especially by about 4.5 folds increase in Ly6cloMrc1+ macrophages and 2.6 folds increase in Ly6cloEar2+ macrophages. Moreover, myeloid cells harbored the richest ligand and receptor (LR) pairs with other cells, particularly for chemokine ligands such as Cxcl9, Cxcl10, Cxcl16 and Yars. However, macrophages with weak response to interferon gamma (IFNg) contributed to rejection chronicization. To conclude, reduction in CD8 T cells, B cells and neutrophils while increasing in Ly6cloMrc1+ macrophages and Ly6cloEar2+ macrophages, may contribute significantly to the progress from AR towards CR.